Analysis of the physical activity of primary school teachers - J.J. Grigoniene; V. Skyriene; N. Margeliene (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The purpose of the study - to identify the ratio of primary school teachers in physical education and sport and to establish their level of physical activity, depending on the length of teaching. The volume of the experimental sample consisted of 74 people. To conduct questionnaires designed questionnaire including 29 questions open and closed. The study found that 77.3% of primary school teachers in Kaunas with 16 to 20 years of work experience were engaged in physical activity and sports. Two - three times a week, they practiced in walking, sports games, cycling, swimming, etc., with this 4-10 hour. All respondents, regardless of their teaching experience, consider physical activity and sports as an excellent means of healing and disease prevention. According to them, they should be engaged in physical activity throughout life and children need to develop positive attitudes towards physical education from their childhood.